(untitled) (Research, Society and Development, 2022)
Objective: The present study seeks to identify the consequences of crack use during pregnancy, to describe the repercussions of crack consumption on women during pregnancy and to discuss the nursing care that can be applied in view of the consequences of crack use in the user during pregnancy. Method: Integrative literature review using the following guiding question: What are the repercussions of crack use during pregnancy. Searches carried out in 2020, without definition of time. Portuguese and English language. Results: 14 articles were selected, from the articles two categories were elaborated for the studied theme: Category 1: Effects of crack in pregnancy and Category 2: Nursing care for pregnant women who use crack. Conclusion: Nursing has a very important role in welcoming and assisting these pregnant users, to provide quality care, without judgments and with qualified professionals, being fundamental to guide these women to have a healthy pregnancy, without the use of drugs, it was possible to identify numerous consequences due to the use of crack during pregnancy, both for the pregnant woman and for the fetus, among them: spontaneous abortion, placental abruption, and fetal death.